Analisis Rasio Likuiditas, Solvabilitas Dan Aktivitas Terhadap Kinerja Keuangan Perusahaan Manufaktur Sub-Sektor Farmasi Periode 2017-2021 - Finna Yuliana; Fathihani (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This study aims to analyzing the effect of liquidity, solvency and activity ratios on the company's profitability which is projected Return On Assets. This research was conducted at pharmaceutical sub-sector companies on the Indonesia Stock Exchange for the 2017-2021 period with a sample of 10 companies. The data analysis technique used is Multiple Linear Regression. Based on the results of the classic assumption test, it shows that there are no problems. The partial test shows that the Current Ratio (CR) variable has no significant effect on the Return On Assets (ROA). Debt to Equity Ratio (DER) variable has a negative effect on the Return On Assets (ROA). Total Asset Turn Over (TATO) has a significant effect on the Return On Assets (ROA). simultaneously the variable CR, DER, TATO affect on ROA